The Design of the Nakhon Nan History Museum - Sriworasa, Siripat; Puchitchawakorn, Taipat (NAJUA: History of Architecture and Thai Architecture, 2024)
Museums in Thailand have official evidence dating back to the reign of King Rama IV, primarily in the form of private museums with limited access to specific groups. These museums gradually spread out from the central areas of governance over time to the present day. They can be divided into two categories: science museums and cultural museums. The latter type is popular in Thailand and often appears in Thai or vernacular architectural styles. This aspect is interesting in terms of architectural style, functionality, and prevailing trends that have persisted up to the present and are expected to continue in the future. This research study focuses on collecting, studying, and classifying information related to the process of establishing museum projects. It does this through case studies of history museum projects in Thailand that have incorporated elements of Thai architecture and vernacular architecture from 1857 to the present. In the early period, museums in Thailand were primarily private collections of the elite and national museums. These included both newly constructed projects and projects that revitalized historical sites and buildings for reuse. This led to the spread of museum popularity and awareness from central administrative areas to key provincial towns through government policies and actions, establishing regional museums. Subsequently, the development of ideas and perceptions led to the establishment of local museums and tourism-oriented museums alongside the trend of establishing memorial museums. These memorial museums often involved adapting or replicating religious sites to show reverence and worship, evolving into commemorative museums for various significant occasions over time. The study results, and classification of data through case studies can explain the factors influencing the choice of Thai and vernacular architectural styles in historical museum buildings in Thailand. These factors include 1) The context and location of the project, 2) the creation and simulation of the atmosphere, 3) concrete expression, and 4) symbolic expression. The results of using these factors as guidelines in the experimental design of the "Nakhon Nan History Museum" aim to create a project that meets the activities and needs by constructing and simulating an atmosphere of the past to enhance and create user experiences. This is done alongside showcasing the local identity that aligns with the surrounding context. The guidelines from this study can be adapted for designing other types of buildings in the future, which aim to present an image or promote the content and objectives of the project through Thai and vernacular architectural styles.